+0

# Help!

+1
122
1
+321

What is 2sqrt(147) + 2sqrt(27) - sqrt(98)

Davis  Mar 2, 2017

#1
+91259
+10

Hi Davis,

look, study, learn :))

2sqrt(147) + 2sqrt(27) - sqrt(98)

To simplify a square root you must look for a square number that goes into it

square numbers are

$$1^1=1 \qquad \text{not helpful though}\\ 2^2=4\\3^2=9\\4^2=16\\etc\\$$

I can see tht

147 = 49*3

27=9*3

98=49*2

so I have

$$2\sqrt{147} + 2\sqrt{27} - \sqrt{98}\\ =2*\sqrt{49*3} \quad+\quad 2*\sqrt{9*3} \quad-\quad \sqrt{49*2}\\ =2*\sqrt{49}*\sqrt3 \quad+\quad 2*\sqrt9*\sqrt3 \quad-\quad \sqrt{49}*\sqrt2\\ =2*7*\sqrt3 \quad+\quad 2*3*\sqrt3 \quad-\quad7*\sqrt2\\ =14\sqrt3 \quad+\quad 6\sqrt3 \quad-\quad7\sqrt2\\ =20\sqrt3 \quad -\quad7\sqrt2\\$$

After you look and study, ask any questions that you want to :)

Melody  Mar 2, 2017
Sort:

#1
+91259
+10

Hi Davis,

look, study, learn :))

2sqrt(147) + 2sqrt(27) - sqrt(98)

To simplify a square root you must look for a square number that goes into it

square numbers are

$$1^1=1 \qquad \text{not helpful though}\\ 2^2=4\\3^2=9\\4^2=16\\etc\\$$

I can see tht

147 = 49*3

27=9*3

98=49*2

so I have

$$2\sqrt{147} + 2\sqrt{27} - \sqrt{98}\\ =2*\sqrt{49*3} \quad+\quad 2*\sqrt{9*3} \quad-\quad \sqrt{49*2}\\ =2*\sqrt{49}*\sqrt3 \quad+\quad 2*\sqrt9*\sqrt3 \quad-\quad \sqrt{49}*\sqrt2\\ =2*7*\sqrt3 \quad+\quad 2*3*\sqrt3 \quad-\quad7*\sqrt2\\ =14\sqrt3 \quad+\quad 6\sqrt3 \quad-\quad7\sqrt2\\ =20\sqrt3 \quad -\quad7\sqrt2\\$$

After you look and study, ask any questions that you want to :)

Melody  Mar 2, 2017

### 9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details